2022
DOI: 10.3390/antiox11122309
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Fermented Malic Acid Facilitates the Production of High-Quality Chicken via Enhancing Muscle Antioxidant Capacity of Broilers

Abstract: Malic acid, an intermediate of the tricarboxylic acid (TCA) cycle, is a promising acidifier with strong antioxidant capacity. This study aimed to evaluate the effects of bio-fermented malic acid (BFMA) on promoting the body health, performance and meat quality of broilers. A total of 288 one-day-old Arbor Acres male broiler chicks were randomly divided into four treatments with six replicates in each. Every replicate had 12 chicks. Four experimental diets contained 0, 4, 8, and 12 g/kg BFMA, respectively. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 69 publications
1
16
0
Order By: Relevance
“…In the current study, dietary 0.8% MA supplementation increased the growth performance and decreased the drip loss of broilers at large-scale rearing. These results were in agreement with our previous study where the ADG, feed conversion ratio, and WHC were all significantly improved by dietary MA in broilers [ 19 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, dietary 0.8% MA supplementation increased the growth performance and decreased the drip loss of broilers at large-scale rearing. These results were in agreement with our previous study where the ADG, feed conversion ratio, and WHC were all significantly improved by dietary MA in broilers [ 19 ].…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, MA administration increased the oxidative fiber percentage and decreased the drip loss of pork [ 18 ]. Meanwhile, the beneficial effects of MA on drip loss were also observed using 288 Arbor Acres (AA) broilers [ 19 ], however, the exact mechanism is unknown. It’s also not sure whether the outputs obtained under experimental conditions could translate into commercial conditions.…”
Section: Introductionmentioning
confidence: 99%
“…47 Interestingly, the genera of Helicobacter were decreased in the group fed the diet supplemented with bio-fermented malic acid. 47 Our results also showed a decrease in Helicobacter in the YJ5 group, indicating that the fermentation product malic acid of L. acidipiscis YJ5 may modulate gut microbiota to play a role. Heliangin, another fermentation product of L. acidipiscis YJ5 could inhibit the expression levels of TNF-α, NO, IL-6, and PGE2 in macrophage cell lysate.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, bio-fermented malic acid could modulate the cecum microbiota of broilers. 47 Interestingly, the genera of Helicobacter were decreased in the group fed the diet supplemented with bio-fermented malic acid. 47 Our results also showed a decrease in Helicobacter in the YJ5 group, indicating that the fermentation product malic acid of L. acidipiscis YJ5 may modulate gut microbiota to play a role.…”
Section: Papermentioning
confidence: 97%
“…This explains their increased feed intake. In addition, TMAE contains soluble carbohydrates, L-malic acid and 1,3-Dihydroxyacetone dimer, etc., which have obvious sweet smell, improve feed palatability and stimulate appetite of broilers ( 30 , 54 56 ). The results of serum biochemistry showed that the ALP content of High group was significantly increased (P<0.05).…”
Section: Discussionmentioning
confidence: 99%